Do the equity holding and soundness of bank underwriters affect issue costs of SEOs? - Suzuki, Katsushi (Journal of Banking & Finance, 2010)
This paper examines the effects of characteristics of bank underwriters on issue costs in seasoned equity offerings in Japan following deregulation in 1999. I find that banks’ holding loans have a negative effect on price discounts and no effect on underwriting fees. However, banks’ equity holdings have no effect on discount rates and a positive effect on underwriting fees. Furthermore, issuers with unhealthy banks pay higher discount rates, are more likely to be weak in their ex-post operating performance, and are less willing to switch underwriters. I conclude that the characteristics of banks have different effects on issue costs.